STRATEGI AWAL PENANGGULANGAN COVID-19 DI NEGARA BERPENDAPATAN MENENGAH KE BAWAH: SYSTEMATIC REVIEW - Mirza Aulia; Atik Nurwahyuni (Jurnal Medika Hutama, 2021)
On December 2019, new type of coronavirus was discovered in Wuhan, China, causing an infectious and dangerous disease that later known as COVID-19. COVID-19 was then declared as pandemic and spread with alarming speed throughout the globe. With rapid and correct measures, the spreading of COVID-19 in a country could be contained and thus eliminating the chance of it to become a heavy burden. However, with limited resources and poor systems, the LMICs was struck with worse situation. This article systematically reviewed the early strategies and responses of LMICs in facing the early stage of pandemic. Systematic review was carried out by identifying literatures on online databases, named ProQuest, ScienceDirect, Scopus, and Wiley Online Library using keywords “COVID-19, strategy, response, and LMIC”. The inclusion criteria were English full-text articles, published from January 2020 to March 2021 with LMICs background. Six articles were obtained using PRISMA flow diagram. Some LMICs were known to be succeeded in combating pandemic on its early stages. The limitations known in LMICs were absence of governmental preparedness, limited resources for preventive and containment measures, and incoherent coordination and communication. Fixing these areas of concern could help LMICs in dealing with similar situation in the future. Prioritizing effective rapid response in early stage to face an issue like the pandemic will help LMICs to ease the health and economic burdens and keep the situation under control.